Resultado inventario de señales verticales según oficio LM-IC-D-0386-19. Municipalidad de Goicoechea - Acosta Hernández, Erick (2024)
UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ingeniería::LanammeUCR